Perancangan dan Implementasi Sistem Monitoring Konsumsi Listrik Tiga Fase: Studi Kasus di Stasiun Geofisika Kelas I Sleman, Yogyakarta - Arfany Dhimas Muftareza; Bagas Pamungkas Saputra; Dimas Aditya Wiranata; Fahar Rafif Arganto; Hilldegard Virgil Richard May; Kholid Amirudin; Muhammad Arya Bintang Pratama; Muhammad Ramdhani Setyo Nugroho; Arif Kurniawan (Yayasan Kita Menulis - JoCPES, 2025)
Efficient electrical energy management is increasingly important in supporting the sustainability of institutional operations and national budget efficiency policies. This study presents the design and implementation of an Internet of Things (IoT)-based 3-phase electricity usage monitoring system implemented at the Sleman Class I Geophysical Station, Yogyakarta. This system integrates a PZEM-004T energy sensor, an ESP32 microcontroller, a 16x2 Liquid Crystal Display, and a W5500 Ethernet module to acquire, process, and transmit real-time electrical parameters, including voltage, current, and kWh. A local network topology is implemented to ensure stable data transmission to a MySQL-based database server, which allows storing data according to a predefined table structure. A web-based user interface is developed to visualize real-time measurements, historical graphs, and electricity cost estimates. Several features are also developed. System evaluation is conducted by comparing the developed instrument with the official PLN kWh meter. Statistical analysis shows an average difference of 0.021 kWh with a standard deviation of 0.02132 kWh. The linear regression results show a slope of 1.000349, an intercept of −3.589572, and a coefficient of determination (R²) of 0.9999988, indicating a near-perfect linear correlation. Error metrics including MAE (0.01934 kWh), RMSE (0.02696 kWh), and MAPE (0.0001885%) confirm the high accuracy and precision of the system. Therefore, the proposed system is reliable for real-time internal energy monitoring and supports data-driven electricity usage optimization.